An integrated simulation environment for testing V2X protocols and applications - Choudhury, Apratim (2018)
Implementation of Vehicle-to-everything (V2X) communication technologies, for traffic management, has been envisioned to have a plethora of far-reaching and useful consequences. However, before any hardware/software infrastructure can be developed and implemented, a thorough phase of testing is warranted. Since actual vehicles and traffic conditions cannot be physically re-constructed, it is imperative that accurate simulation tools exist in order to model pragmatic traffic scenarios and communication amongst the participating vehicles. In order to realize this need of simulating V2X technology, we have created an integrated simulation environment that combines three software packages, VISSIM (traffic modelling), MATLAB (traffic management applications) and NS3 (communication network simulation). The combination of the simulators, has been carried out in a manner that allows on-line exchange of data amongst them. This enables one to visualize whether a traffic management algorithm creates the desired effect and also the efficacy of the communication protocol used. In order to test the simulator, we have modelled the Green Light Optimized Speed Advisory (GLOSA) application, whose objective is communication of the present traffic signal phase information to oncoming vehicles using a transmitting unit installed on the signal itself. This information will allow the vehicles to calculate the desired speeds necessary to cross the relevant intersection without stopping. Therefore, a “Green Wave” can be created for all vehicles without the need to coordinate traffic signal timers, which can be rather complex in a multiple intersection traffic corridor.